Switched reaction specificity in polyesterases towards amide bond hydrolysis by enzyme engineering. Issue 62 (7th November 2019) - Biundo, Antonino; Subagia, Raditya; Maurer, Michael; Ribitsch, Doris; Syrén, Per-Olof; Guebitz, Georg M.
Abstract : The constitution of a water network for the nitrogen inversion mechanism by H-bonding can increase amide-containing substrate acceptance of polyesterases. Abstract : The recalcitrance of plastics like nylon and other polyamides contributes to environmental problems ( e.g. microplastics in oceans) and restricts possibilities for recycling. The fact that hitherto discovered amidases (EC 3.5.1. and 3.5.2.) only show no, or low, activity on polyamides currently obstructs biotechnological-assisted depolymerization of man-made materials. In this work, we capitalized on enzyme engineering to enhance the promiscuous amidase activity of polyesterases. Through enzyme design we created a reallocated water network adapted for hydrogen bond formation to synthetic amide backbones for enhanced transition state stabilization in the polyester-hydrolyzing biocatalysts Humicola insolens cutinase and Thermobifida cellulosilytica cutinase 1. This novel concept enabled increased catalytic efficiency towards amide-containing soluble substrates. The afforded enhanced hydrolysis of the amide bond-containing insoluble substrate 3PA 6, 6 by designed variants was aligned with improved transition state stabilization identified by molecular dynamics (MD) simulations. Furthermore, the presence of a favorable water-molecule network that interacted with synthetic amides in the variants resulted in a reduced activity on polyethylene terephthalate (PET). Our data demonstrate the potential of using enzyme engineering to improve the amidase activity for polyesterases to act on synthetic amide-containing polymers.